The Effect of Service Quality Dimension on Taxpayers’ Satisfaction (Study at Howard Tax Consultant) - Gladys Greselda Gosal; Christina Whidya Utami (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
This research aims to explore the impact of service quality towards the satisfaction of taxpayers who use the services of Howard Tax Consultant. Dimensions of the service quality that are used as independent variables are flexibility, reliability, assurance, tangibles, and responsiveness, meanwhile the dependent variable is taxpayers’ satisfaction. All members of the population are taken as the sample of the research, with total of 50 respondents, among those are 35 individual taxpayers and 15 corporate taxpayers. Data was collected through questionnaire with 24 indicators with Likert scale, and was analyzed using multi-linear regression analysis. The result of multi-linear regression analysis shows that flexibility, reliability, assurance, tangibles, and responsiveness are significantly and positively correlated to the satisfaction of taxpayers who use the services of Howard Tax Consultant, and therefore it is concluded that all the hypothesis in this research are upheld.